Readiness of New Students Learning in The Network: Case Study - Kartini Kartini; Sucahyo Mas'an Al Wahid; Agustinus Toding Bua (IJECA (International Journal of Education and Curriculum Application), 2020)
A system that gives freedom of time, place and is not only oriented to the teaching staff who are currently also looking for as many digital references as possible to use in the application of every online course. However, the use of platforms and the use of technology need to be supported by adequate facilities and infrastructure so that the implementation of online learning can be carried out properly. The purpose of this study was to determine the extent of the readiness of new students to face online sharing in terms of facility readiness and platform utilization. The research method used a qualitative approach to survey techniques with sampling of the population using a snowball. Instruments in the form of documentation and structured interviews. The results showed that 95% of the new students in primary teacher education program majors at University of Borneo Tarakan were facilitated by supporting facilities and infrastructure to face online learning and 80% were familiar with the platforms used in general but there was no BEL UBT platform used by students. The solution provided, the existence of socialization and restrictions on the use of applications in teaching and learning activities online.